KONSUMSI DAN BATASANNYA DALAM PANDANGAN MUSLIM KONTEMPORER - Saoki . (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2015)
This study wants to answer two problems. First, What is the concept of consumer behavior setting according to Yusuf al-Qardlawi’s thinking? Secondly, how is the implementation of the concept of thought of Yusuf al-Qardlawi? This research uses normative approach (theory) research. It is hoped that this approach can be seen through the Islamic concept of consumption and in the implementation of the view of al-Qardlawi. The research concludes that according to Yusuf Qardlawi Islam gives the basic norm that underlies the behavior of consumption, ie avoiding or curmudgeonly miser nature, should not be wasteful action and should have simple property and behavior. While, the implementation of the above concepts; The first not conducting the stingy or griping to provide donation either mandatory or Sunnah, both for themselves and for their families, for communities and for the fi sabilillah (in the way of Allah). Secondly, no action redundant, which means it does not spend his money for something without any benefit and for the things that are forbidden, including spending his money to excess that exceeds the limit in terms of kosher, and the last is the attitude and behavior should be modest implanted in every human daily life, by being midway between the curmudgeonly attitude and the attitude of wasteful and excessive attitudes including attitude luxuries.